Knowledge of youth about HCV virus infection on an example of research of the students in high school and basic professional school - Sierpińska, Lidia; Chrapko, Michalina; Rząca, Marcin (Journal of Education, Health and Sport, 2017)
Introduction. Infection with HCV is an important clinical problem diagnostic, epidemiological, economic and social in Poland and in the world. Purpose of the work. Good knowledge of the basic school and youth Professional on infection with HCV. Material and method. The study was conducted in three secondary schools (high school, technical school, vocational school principal) in the story. The study included 109 students. Research was a diagnostic survey, questionnaire, and tools were the original questionnaire surveys that include questions about demographic and social characteristics and standard questionnaire survey by the Polish group of experts HCV. Statistical analysis was conducted using the statistical package StatSoft Statistica 12.0 PL and Microsoft Office. The results. The vast majority of young people (82 respondents - 75.2%) knew that the HCV virus is the cause of hepatitis c. Girls more often (81.8%) than boys (64.8%) knew that the HCV virus can infect through contact with infected blood. More than a third of boys (37.0%) and girls (36.4%) knew that in Poland about 700 thousand people are infected with HCV. A large group of young people (80.7%) knew that everyone is vulnerable to infection with HCV. Girls more often (76.4%) than boys (59.3%) correctly reported examples of situations which may lead to infection. More than half of the test (67.0%) knew that by doing a blood test for the presence of anti-HCV antibodies, you can verify that you are infected with HCV and 67.0% of respondents knew that there is no developed hepatitis b vaccine hepatitis C. Less than half of the test (44.0%) had knowledge of the possibility of cure people infected with HCV. Conclusions. Investigated young people had a high level of knowledge about the causes of hepatitis c. Should motivate school students to broaden knowledge about the prevention of infection with HCV, risk and sources of infection with HCV with particular attention to drug addicts, to beauty salons and hairdressing salons.